187k views
1 vote
Plzzzz need answers​

Plzzzz need answers​-example-1
User AlloVince
by
5.8k points

1 Answer

5 votes

Answer:

1. (x,y)→(y,-x)

2. (x,y)→(-y,x)

3. (x,y)→(-x,-y)

Explanation:

1. Rotation 90° clockwise (or 270° counterclockwise) about the origin changes x into y and y into -x, so it has the rule

(x,y)→(y,-x)

2. Rotation 90° counterclockwise (or 270° clockwise) about the origin changes x into -y and y into x, so it has the rule

(x,y)→(-y,x)

3. Rotation 180° clockwise about the origin changes x into y and y into -x, so it has the rule

(x,y)→(-x,-y)

Here you can apply rotation by 90° clockwise twice, so

(x,y)→(-y,x)→(-x,-y)

User Eugeniu Torica
by
5.6k points